Masonry structural behaviour at different scales under compressive loading - Mohammed, A.; Hughes, T. G. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2008)
This paper discusses the effect of scale on masonry structural behaviour under compressive loading. Reduced scales have been employed to understand masonry structural behaviour over the years, because testing prototype masonry structures is both costly and difficult to control in terms of instrumentation. A programme of tests has been carried out at four scales namely prototype, half, fourth and sixth scale under compression with a view to understanding how each of these conditions affects masonry structural behaviour over the range of scales enumerated. The results show that masonry compressive strength is increased as the scale is reduced but the stiffness is not markedly influenced.